2018
DOI: 10.1167/tvst.7.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Is Ahmed Glaucoma Valve Consistent in Performance?

Abstract: PurposeTo investigate the mechanism of action and consistency in flow characteristics of the Ahmed glaucoma valve (AGV) under simulated physiological conditions in-vitro and to evaluate whether resistance during priming has any effect on performance of the device.MethodsEach newly opened AGV device was connected to a digital manometer and was primed with normal saline. The device was then placed in a saline bath and connected to an open manometer, a digital manometer, and an infusion pump. Saline was infused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… 1 , 6 , 9 In addition to opening and reducing the valve resistance in the AGV before its implantation, another purpose is to remove air in the device and ensure that there are no manufacturing defects. 8 Cheng et al 9 measured this priming pressure and reported an average of 3000 mm Hg; even with priming 3 times, the pressure greater than priming did not damage the function of the silicone-plate valve of the AGV. 9 In our experiments, the initial priming pressure exceeded the measurement scale in some devices; thus, the observation reproduced the previous report that showed an extremely high initial priming pressure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 1 , 6 , 9 In addition to opening and reducing the valve resistance in the AGV before its implantation, another purpose is to remove air in the device and ensure that there are no manufacturing defects. 8 Cheng et al 9 measured this priming pressure and reported an average of 3000 mm Hg; even with priming 3 times, the pressure greater than priming did not damage the function of the silicone-plate valve of the AGV. 9 In our experiments, the initial priming pressure exceeded the measurement scale in some devices; thus, the observation reproduced the previous report that showed an extremely high initial priming pressure.…”
Section: Discussionmentioning
confidence: 94%
“… 6 , 7 Several in vitro studies have determined the pressure required to open the valve of the device (referred to as priming) when it was first used. 8 , 9 However, the flow characteristics after the initial priming have not been fully tested. Initial priming is done intra-operatively by injecting about 1 cc of ophthalmic irrigation fluid (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the minor IOP fluctuations caused by fluctuating flow, the model assumes a consistent fluid outflow via the AGV and thus a consistent post-operative IOP level when in fact, both in-vivo and in-vitro, AGV function has been shown to be inconsistent 31 . Furthermore, clinically it is common to observe a ‘hypertensive’ phase three to six weeks post-operatively that is thought to be caused by encapsulation of the bleb 32 .…”
Section: Resultsmentioning
confidence: 99%
“…The internal diameter of the tube is 0.3 mm and allows the flow of aqueous humor from the anterior chamber through the tubing to the plate by either valved (Ahmed and Krupin) 5,35,36,39,40 or nonvalved (Baerveldt and Molteno) 41,42 mechanisms. Valved shunts open when IOP rises over approximately 12 mm Hg with subsequent “bleb” formation for systemic reabsorption 43,44 …”
Section: Filtering Proceduresmentioning
confidence: 99%